Effect of tungsten on the vacancy behaviors in Ta–W alloys from first-principles calculations. (February 2020) - Lv, Yini; Hu, Kaige; Huang, Zheng; Cao, Zelin; Wen, Shulong; Zhao, Yong; Pan, Min; Deng, Huiqiu
Abstract: Alloying elements play an important role in the design of plasma facing materials with good comprehensive properties. Based on first-principles calculations, the stability of alloying element W and its interaction with vacancy defects in Ta–W alloys have been studied. The results show that W tends to distribute dispersedly in Ta lattice, and is not likely to form precipitation even with the coexistence of vacancy. The aggregation behaviors of W and vacancy can be affected by their concentration competition. The increase of W atoms has a negative effect on the vacancy clustering, as well as delays the vacancy nucleation process, which is favorable to the recovery of point defects. Our calculations are in consistent with the defect evolution observed in irradiation experiments in Ta–W alloys. The results suggest that W is a potential repairing element that can be doped into Ta-based materials to improve their radiation resistance. Highlights: W tends to distribute dispersedly in Ta lattice, and is not likely to form precipitation with the coexistence of vacancy. The aggregation behavior of W and vacancy can be affected by their concentration competition. The increase of W atoms has a negative effect on the vacancy clustering, and delays the vacancy nucleation.